Analysis of the opening scene and introductory part of the epic poems: Banu ghoshap-nama, Borzu-nama, Bahman-nama and Garshasap-nama, based on the theory of Propp - کاظم دزفولیان; معصومه طالبی (تاریخ ادبیات)
The Morphology of Fairy Tales, by Vladimir Propp, a Russian linguist, is an epoch-making work that has attracted the attention of critics for many decades since its appearance. Despite the fact that the position of this book fluctuated in the bright shadow of formalism and structuralism, it was finally introduced as a work whose function is the transition from formalism to structuralism. Propp, after examining a class of folk tales, under the title of fairy tales, put forward the theory that the stories have different forms, with different characters, but have a primary plot. In this article, relying on this approach, it is tried to put aside the microscopic view of the literature and look at the overall structure of the epic poems with an inclusive* and at the same time modern view and show how the proposed done by Propp, can be traced in a surprising way, especially in the opening scenes of these poems and the introductory part of the stories.